An Analysis of Cultural Terms Translation in ‘Chef’ Movie Script - Intan Firdaus; Gayus Immanuelle Putranda Nauly (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
The focus of this study was on the translation of cultural terminology found in the "Chef" movie script. The goals were to determine the cultural category, the translation techniques used, and the translation quality. The data for this analysis were words, phrases, and sentences, hence the descriptive qualitative method was utilized. Purposive sampling was used by the researchers, and got 28 sets of data to analyze. The movie script contained four out of five cultural categories: material (75%), concept and social organization (14.28%), ecological (7.14%), and gesture and habit (7.14%). (3.57%). Only four of the 18 translation strategies were used to translate the cultural terms: pure borrowing (75 %), literal translation (39.28 %), established equivalence (7.14 %), and adaptation (7.14 %) (3.57%) The quality of the translation study revealed that 27 data (96.42 %) were accurately translated into Indonesian, and that 28 data (100%) were acceptable and highly readable.